Comparison of two methods in the peripheral nerve block application used in foot surgery: USG-guided and anatomical landmark-guided. - Mesut Uluöz; Ümmühan Eren Herdem (Acta Medica Alanya)
Aim: Ankle peripheral nerve block is applied by two methods. These are peripheral block that is performed using USG-assisted and anatomical landmarks that do not require the use of Ultrasonography (USG). In our study, we aimed to compare these two methods applied in foot surgeries retrospectively.Methods :Peripheral block patients performed with the USG-guided (group 1) were 20, anatomical landmarks- guided (group 2) were 20. In both groups, 40 cc of anesthetic mixture was used (bupivacaine + lidocaine). The recorded information of the patients were as follows: Block application time (BAT), surgery readiness time (SRT), duration of surgery (DoS), duration of block anesthesia (DBA) and intraoperative-postoperative Visual Analogue Scale (VAS). The results of the VAS applied to the patients postoperatively were obtained. Patients were contacted by phone and asked if they were satisfied with the anesthesia.Results : The BAT and DBA values of the patients in Group 1 were high. SRT and VAS 6 values of the patients in group 2 were high. No significant difference was found between the groups in other parameters. No additional dose of anesthetic was needed in group 1 during the intraoperative period. In group 2, local additional dose was administered to 3 patients.Conclusion: Peripheral block preparation USG-guided takes a long time. However, it is more comfortable during surgery. The USG-guided peripheral nerve block is more advantageous when considering the possibility of prolonging the duration of surgery for any reason and early postoperative pain control after surgery.